Tratamento com canabidiol atenua efeitos compulsivo e ansiogênico promovidos pelo consumo de dieta rica em carboidrato em camundongos Balb/C - Anna Paula Marçal de Melo (2020)
Obesity and its comorbidities represent a significant problem in the public health of the worldwide. The increase in consumption of processed foods, with low satiety capacity and high energy imbalance, is closely related to the development of obesity. In obese people, the white adipose tissue has characteristics of a low-intensity inflammatory state, which could be associated with the development of obesity and its comorbidities, such as type 2 diabetes, metabolic syndrome. Moreover, peripheral inflammation is associated with the development of anxiety and compulsion disorders. In this sense, cannabidiol (CBD), the primary non-psychoactive phytocannabinoid present in the Cannabis sativa plant, emerges as a potential therapeutic drug for the treatment of psychiatric diseases. In this study, we verified whether acute or subchronic treatment with CBD would be able to attenuate the anxiety-like and compulsive-like behaviors observed after chronic consumption of a carbohydrate-rich (HC) diet in mice. Balc/C mice received a control or HC diet for 12 weeks. The HC diet consisted of 40% condensed milk, 40% standard diet, 12% refined sugar, and 8% water. After this diet period, the animals were divided into two groups: vehicle and CBD and, had their behavior evaluated in the Marble Burying test (MB) and Novel Suppressing Feeding test (NSF). The chronic consumption of the HC diet induced an anxiogenic-like behavior in the NSF test and a compulsive-like behavior in the MB test. The pre-treatment with CBD (30 mg/kg) attenuated such effects. Our data reinforced the deleterious effects induced by chronic consumption of the HC diet in the compulsive and anxious behaviors and the potential of the CBD as a potential drug treatment. However, the mechanisms responsible for CBD effects need to be clarified.